Development of a course for training in modern cloud technologies - A. V. Stavitskiy; I. G. Ashavskiy; D. V. Volkov (Открытое образование (Москва), 2019)
Purpose of the study. The aim of the study is to create a course on modern cloud technologies based on the openstack cloud virtualization platform.The popularity of the openstack platform makes it the main platform for building cloud technologies in many large Russian and international companies in various business areas.In the process of developing the course, the goal was to adhere to the principles of open education.Development of the course was motivated by the growing popularity of cloud technologies in most IT companies and demand for qualified specialists in this field.Materials and methods. Analytical reports in the field of modern trends in the development of cloud technologies, materials on current trends in hiring employees by industry, as well as official documentation on projects, used in the course are selected as the main materials for the study.During the development and implementation of the project, the following pedagogical techniques were used:acquisition of new knowledge based on pre-existing one;teamwork and demonstration of communication skills; making educational hypotheses to resolve problematic situations;planning to achieve the goal (getting results);private methods of students’ learning activities (detailing the tasks, initial conditions and the course of the study).Results. As a result of the study, the necessity of creating an educational course for students was substantiated, and a special course was developed for teaching the openstack cloud virtualization platform, which includes the necessary materials (presentations, lectures, seminars, as well as a platform and laboratory stands for students with access via the Internet).A special course web page was created where potential students have the opportunity to familiarize themselves with the description and basic components of the course, send a request for participation, and also get access to the materials (after confirmation of the participant by the administrator).Every year, the developed materials, the platform and laboratory stands are updated due to the release of new versions of openstack, adding new functionality and updating business needs.Conclusion. In conclusion, a decision was formulated on the advisability of creating a special course for students and specialists. The developed course was tested in leading higher educational institutions of the country, and is a convenient tool for both students and companies, interested in qualified personnel in the field of cloud technologies.The special course was tested on students of the Faculties of Computational Mathematics and Cybernetics, the Faculty ofMechanics and Mathematics of Lomonosov Moscow State University, Financial University under the Government of the Russian Federation, Plekhanov Russian University of Economics, Innopolis University and Moscow Technical University of Communications and Informatics.According to the results of the special course, students were selected for internships and practical training, which confirmed the effectiveness of the developed course.